1998
DOI: 10.1097/00005392-199810000-00172
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Escherichia Coli Isolates From Patients With Symptomatic and Asymptomatic Bacteriuria and Neuropathic Bladders Due to Spinal Cord and Brain Injuries

Abstract: Chronic bacteriuria is a common occurrence among spinal-cord injury patients and others with neuropathic bladders. If bacteria are present in the urinary tract, the patient may develop symptoms of infection or remain asymptomatic. We have compared virulence properties of 28 Escherichia coli isolates from patients with symptomatic urinary tract infections (UTI) and 29 E. coli isolates from patients with asymptomatic bacteriuria (ABU). Bacteria from patients with symptomatic UTI were more likely to be hemolytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…55 In terms of VFs, it has been reported that there was a signifi cant difference only in the prevalence of Hly between symptomatic UTI and ASB, whereas there was no difference in adhesion-related VFs among patients with neurogenic bladder caused by spinal cord or traumatic brain injury. 56 Another study reported that E. coli strains from pregnant women with ASB were less likely to carry adhesin-related and toxic genes than those from patients with community-acquired cystitis. 57 Moreover, in a recent article, resistance to quinolones was reported to be associated with a decrease in the presence or the expression of some VFs, such as Hly, CNF1, and type 1 pili, in UPEC, indicating that antibiotic pressure may have affected the population and predominance of bacterial strains causing UTIs.…”
Section: Distribution Of Vfs In Cystitis Pyelonephritis and Prostatmentioning
confidence: 99%
“…55 In terms of VFs, it has been reported that there was a signifi cant difference only in the prevalence of Hly between symptomatic UTI and ASB, whereas there was no difference in adhesion-related VFs among patients with neurogenic bladder caused by spinal cord or traumatic brain injury. 56 Another study reported that E. coli strains from pregnant women with ASB were less likely to carry adhesin-related and toxic genes than those from patients with community-acquired cystitis. 57 Moreover, in a recent article, resistance to quinolones was reported to be associated with a decrease in the presence or the expression of some VFs, such as Hly, CNF1, and type 1 pili, in UPEC, indicating that antibiotic pressure may have affected the population and predominance of bacterial strains causing UTIs.…”
Section: Distribution Of Vfs In Cystitis Pyelonephritis and Prostatmentioning
confidence: 99%